Ação solvente do salicilato de metila sobre resilon e guta-percha - Nascimento, Camila Almeida [UNESP]; Tanomaru-Filho, Mário [UNESP]; Sant'Anna Júnior, Arnaldo [UNESP]; Bosso, Roberta [UNESP]; Faria, Gisele [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (My University, 2012)
Objective: The aim of this study was to evaluate the action of methyl salicylate in dissolving Resilon and gutta-percha. Material and method: Ten discs of Resilon, Alpha gutta-percha and ProTaper gutta-percha were prepared (10 mm diameter × 1 mm thick) and kept at 37 °C for 48 hours. Each sample was weighed in a balance of accuracy determining the initial mass. The specimens were immersed in methyl salicylate or xylene (control) for 5  minutes, rinsed in water for 30 minutes, dried and subsequently weighed in 24 hours intervals until the stabilization of weight (final mass). The solvent capacity was expressed by the difference between the final and initial mass. The data were analyzed by using ANOVA and Tukey test with significance level of 5%. Result: The results showed that the methyl salicylate was more effective on Resilon than on gutta-percha (p < 0.05). Methyl salicylate and xylene had similar solvent action on Resilon (p > 0.05). The xylene showed better performance on gutta-percha than methyl salicylate (p < 0.05). Conclusion: It was concluded that methyl salicylate did not show solvent action on gutta-percha, however it showed effectiveness in dissolution of Resilon. Thus methyl salicylate can be a possible alternative to the use of xylene during endodontic retreatment of teeth obturated with Resilon.

Objetivo: O objetivo deste estudo foi avaliar a ação do salicilato de metila na dissolução de Resilon e guta-percha. Material e método: Dez discos de Resilon, guta-percha (Alpha) e guta-percha (ProTaper) foram preparados (10 mm de diâmetro × 1 mm de espessura) e mantidos a 37 °C por 48 horas. Cada amostra foi pesada em uma balança de precisão, determinando a massa inicial. Os espécimes foram imersos em salicilato de metila ou xilol (controle) por 5 minutos, lavados em água por 30 minutos, secos e, posteriormente, pesados em intervalos de 24 horas, até a estabilização da massa (massa final). A capacidade solvente foi expressa pela diferença entre a massa final e a inicial. Os dados foram submetidos à análise de variância e teste de Tukey, com nível de significância de 5%. Resultado: Os resultados mostraram que o salicilato de metila foi mais efetivo sobre o Resilon do que sobre a guta-percha (p < 0,05). A capacidade solvente do salicilato de metila foi semelhante à do xilol sobre o Resilon (p > 0,05). O xilol mostrou melhor atuação sobre a guta-percha em comparação ao salicilato de metila (p < 0,05). Conclusão: Concluiu-se que o salicilato de metila não apresenta atuação solvente sobre guta-percha, sendo eficaz na dissolução do Resilon. O salicilato de metila demonstra ser alternativa ao uso do xilol durante o retratamento endodôntico de dentes obturados com Resilon.
Solvent action of methyl salicylate on resilon and gutta-percha
Keywords: Endodontics; Gutta-percha; Xylenes; Dissolution; Endodontia; Guta-percha; Xilenos; Dissolução